Morphological Characteristics of the Oropharyngeal cavity in White-breasted Waterhen (Amaurornis phoenicurus) - Varsha Gupta; M. M. Farooqui; Archana Pathak; Aayushi Rathore; Harsh Veerbhan; Anand Singh (Indian Journal of Veterinary Anatomy, 2025)
The present study represents the anatomical description of theoropharyngeal cavity of the white breasted water hen. The oropharyngeal cavity of the White-breasted Waterhen is part of its unique anatomical features that help in its feeding and vocalization.The oropharyngeal cavity consisted of roof formed by incomplete hard palate cranially and the pharynx caudally and floor formed by mandible, occupied by the tongue cranially and laryngeal mound caudally. The beak was thinner and more pointed, adapted for foraging in water and mud. The upper and lower beak was almost equal in size, with triangular shaped pointed apex. The roof/palate was divided into two regions: a small rostral non-papillary and a large caudal papillary region. The rostral region was characterized by the presence of three longitudinal ridges.The papillary crest had two paramedian longitudinal papillary rows, the paramedian ridges were separated from the median ridge by shallow grooves on each side. There was a transverse papillary row between the caudal border of the infundibular cleft and oesophagus. The floor of the oropharyngeal cavity was filledwith the tongue and the laryngeal mound. The tongue was typically slender and pointed with a tapered apex that carries a terminal lingual nail. There were no macroscopic lingual projections on the dorsal surface of the tongue. The lingual body had a median lingual sulcus. Macroscopically, the transverse papillary crest with the large mechanical caudally directed conical papillae was located between the lingual body and thelingual root.The lingual root was consisted of four parts: round, triangular, semilunar and depressed parts. The laryngeal mound had an elongated glottic fissure, carrying a single row of papillae at the rear edge. There were caudally directed mechanical large conical pharyngeal papillae at the caudal border of laryngeal mound. The pharyngeal papillae were arranged as W-shaped structure. The pharynx was narrower, longer and more specialized for swallowing small food material